Problematika Waktu Tunggu Hukuman Mati di Indonesia Ditinjau dari Undang-Undang dan Hak Asasi Manusia - Ananda Fajar Subakhti; Ilham Kurniawan Dartias (Legalitas: Jurnal Hukum, 2026)
The large number of death row inmates in Indonesia who are awaiting execution has raised significant public concern. This concern arises from the perception that the prolonged delay in carrying out death sentences is inconsistent with the principles of human rights. Individuals who have been lawfully sentenced to death by a final and binding court judgment are also required to endure prolonged imprisonment while awaiting execution. Consequently, death row inmates are perceived as serving two forms of punishment simultaneously: imprisonment and capital punishment. In practice, the phenomenon of the death row waiting period extends beyond the time required for the exhaustion of legal remedies and/or the submission of petitions for presidential clemency. Rather, the prolonged waiting period has evolved into a distinct form of punishment for death row inmates. During this period, inmates frequently experience inhumane treatment resulting from overcrowded correctional facilities and the State’s failure to adequately guarantee their fundamental rights. The State's omission in providing basic necessities, maintaining correctional institutions within reasonable capacity, preventing ill-treatment, safeguarding the physical and mental health of inmates, and ensuring legal certainty regarding the timing of executions—often allowing inmates to remain on death row for decades—places such individuals in conditions that are incompatible with the principles of humanity and human dignity. Accordingly, this study seeks to contribute to a better understanding of the phenomenon of the death row waiting period in Indonesia and to examine the appropriate responses expected from both the Executive and the Legislature in order to prevent prolonged uncertainty for inmates awaiting the execution of capital punishment.